Plasma induced Fe-NX active sites to improve the oxygen reduction reaction performance - Rao, Peng; Wang, Tian-Jiao; Li, Jing; Deng, Pei-Lin; Shen, Yi-Jun; Chen, Yu; Tian, Xin-Long (Advanced Sensor and Energy Materials, 2022)
Rational design of high-efficient and low-cost catalysts as alternatives to Pt-based catalysts toward the oxygen reduction reaction (ORR) is extremely desirable but challenging. In this work, Fe@NCNT is firstly synthesized via the one-pot pyrolysis method, then Fe-NX active species are in-situ created on the prepared Fe@NCNT by a feasible “plasma inducing” strategy to synthesize the resulting catalyst (Fe@NCNT-P) for ORR. The morphology of Fe@NCNT-P is perfectly inherited by the derived carbon precursor, resulting in the core-shell structure of carbon-coated Fe and a mesoporous dominant nanostructure with a high specific surface area of 536 m2 g−1. The resultant Fe@NCNT-P catalyst exhibits remarkable ORR activity and durability, as well as outstanding performance in assembled zinc-air battery (ZAB) test with a peak power density of 240 mW cm−2. This work not only reports a novel and robust ORR catalyst, but also proposes a simple and effective strategy to improve the ORR electrocatalytic performance. [Display omitted] •A feasible “plasma inducing” strategy is proposed to form the Fe-NX species.•The in-situ fabricated Fe-NX species is beneficial to the activity of the catalyst.•The catalyst delivers remarkable oxygen reduction reaction activity and stability.